Caracterização fenológica, fisíco-química e fitoquímica de cultivares de marmeleiro - Manica-Berto, Roberta (2009)
Quince shows high genetic variability regarding plant vigor, productivity, flowering, fruit quality. In order to characterize the differences among cultivars, considering the phenological characteristics of the tree, the physicochemical and phytochemical compounds of in natura fruits, this study aimed to describe the phenological stages of the quince and evaluate 21 quince cultivars regards to physicochemical and phytochemical properties. The established phenological scale according BBCH scale for the twenty one cultivars of C. oblonga contains eight stages of development. The stages observed were: 0 - bud development; 1 - Development of the leaves, 3 - Development of shoots, 5 - Emergence of the inflorescence, 6 - Flowering; 7 Development of fruits; 8 - ripening of fruits, 9 - Senescence. The cultivars Champion, Kiakami and Portugal show a different physical-chemical profile whether compared to the others. While the cultivars Zuquerinetta, D'Angers, Prolonged, Orange, Bereckzy, Smyrna, Mendoza Inta-37 have a very similar phytochemical profile. Carotenoid and phenol contents are higher in the peel than the pulp, resulting in a higher antioxidant capacity of the shell.